What drive the local incidence of crime, shadow economy and resource-related conflicts in Mindanao, Philippines? Evidence of spillover effects. Issue 1 (2nd January 2019) - Capuno, Joseph J.
Abstract: Together with Indonesia, Sri Lanka and Thailand, Philippines is among the Asian countries with long history of violent subnational or local conflicts. These conflicts have also exacted heavy tolls in terms of loss in human lives, economic welfare and public resources. Towards a better understanding of local conflicts in the Philippines, we estimate negative binomial regression models using a panel of cities and municipalities in the Autonomous Region of Muslim Mindanao for the period 2011–2016 to examine the pattern of spillover effects. We find strong evidence that for an average locality the incidence of conflicts related to crime, shadow economy or resource (and other unclassified) are influenced positively by the aggregate level of hostilities in its contiguous neighbors. The types of hostilities in the neighbors or the number of neighbors have no significant effects. The policy implication is to contain conflicts at once and where they happen to prevent spillover.